(NkONSU\LO(B: [(NrOMAN(B] / s (N~ASTX (B2s - (NsAND(B, (NvORVs ((NmINSK(B: s "(NbELORUSSKAQ SOWETSKAQ \NCIKLOPEDIQ(B" (NIMENI pETRUSQ bROWKI(B, s, 1989)
(NwTOROJ TOM [IROKOIZWESTNOGO ROMANA v(B. (NsAND O SUDXBE MOLODOJ TALANTLIWOJ PEWICY(B.s
rus
Keywords: (NiSTORI^ESKIJ ROMANs; (Nl@BOWNYJ ROMANs -- (NsOCIALXNO(B-(NPSIHOLOGI^ESKIJs